2022
DOI: 10.1002/mp.16083
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity correction of fluorescent nuclear track detectors using alpha particles: Determining LET spectra of light ions with enhanced accuracy

Abstract: Background: Radiation fields encountered in proton therapy (PT) and ionbeam therapy (IBT) are characterized by a variable linear energy transfer (LET), which lead to a variation of relative biological effectiveness and also affect the response of certain dosimeters. Therefore, reliable tools to measure LET are advantageous to predict and correct LET effects. Fluorescent nuclear track detectors (FNTDs) are suitable to measure LET spectra within the range of interest for PT and IBT, but so far the accuracy and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…more elaborated conversion methods), which is not within the scope of this work. The LET Si values calculated in the present work are in line with those reported in Muñoz et al (2023), since both investigations were carried out at the HIT facility. Building upon the aforementioned studies, our study has demonstrated a similar and even superior performance when considering the entire obtained LET Si range of 0.77 keV µm −1 to 93.16 keV µm −1 of four ion types with an absolute accuracy range of 0.8% to 6.6%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…more elaborated conversion methods), which is not within the scope of this work. The LET Si values calculated in the present work are in line with those reported in Muñoz et al (2023), since both investigations were carried out at the HIT facility. Building upon the aforementioned studies, our study has demonstrated a similar and even superior performance when considering the entire obtained LET Si range of 0.77 keV µm −1 to 93.16 keV µm −1 of four ion types with an absolute accuracy range of 0.8% to 6.6%.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, passive detectors such as FNTDs are also employed for experimental purposes. Recently, FNTDs were used to determine the LET water values of therapeutic ions (Muñoz et al 2023). When conducting a coarse conversion of these LET water values to LET Si (Rosenfeld 2016) with the basic goal of comparing the measured range of track-averaged LETs for the monochromatic ion beams (free in air) that are therapeutically available at HIT, a range of 0.87 keV µm −1 to 93.90 keV µm −1 is obtained with an accuracy range of 0.3%-17%.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence intensity is related to the LET through a calibration curve, as shown in figure 3. The reference LET values were estimated analytically from the residual energy at the detector surface, as detailed in Muñoz et al (2023). Hence, the calibration curve does not represent an average quantity, as it is associated to single particles from mono-energetic beams.…”
Section: Let Determination With Fntdsmentioning
confidence: 99%
“…Hence, the calibration curve does not represent an average quantity, as it is associated to single particles from mono-energetic beams. For consistency, the calibration curve used in this work was determined from data obtained after re-scanning detectors exposedto mono-energetic protons, 4 He-and 12 C-ions in a previous work (Muñoz et al 2023), but following the scanning protocol used in this work. From the fluorescence intensity, the LET in water of each track was calculated through the calibration curve.…”
Section: Let Determination With Fntdsmentioning
confidence: 99%
See 1 more Smart Citation